1979
DOI: 10.1017/s0021859600037977
|View full text |Cite
|
Sign up to set email alerts
|

The growth and development of cowpeas (Vigna unguiculata) under tropical field conditions: 1. Leaf area

Abstract: SUMMARYThe pattern of leaf growth and death was followed in stands of cowpea grown in the field at Ibadan, Nigeria. Temperature affected this pattern. Leaf area index increased quicker and leaf death started sooner during warm seasons. Individual leaves died while pods at the same node were filling. The rate of leaf appearance increased with temperature and the duration of expansion of individual leaves decreased so that a constant number of leaves were expanding at one time. The mean rate of expansion of indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
1
4

Year Published

1981
1981
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 19 publications
2
20
1
4
Order By: Relevance
“…Soon after, an accelerated vegetative growth was observed, with maximum values of LAI, observed and simulated, varying from 3 to 4.3, in 1997 and 1998, respectively. The number of days to reach the maximum LAI values ranged from 45 to 60 DAP, which is in agreement with the results obtained by Littleton et al (1979). This variation may be associated with differences in planting date and seasonal variation in the air temperature (Summerfield et al, 1983).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Soon after, an accelerated vegetative growth was observed, with maximum values of LAI, observed and simulated, varying from 3 to 4.3, in 1997 and 1998, respectively. The number of days to reach the maximum LAI values ranged from 45 to 60 DAP, which is in agreement with the results obtained by Littleton et al (1979). This variation may be associated with differences in planting date and seasonal variation in the air temperature (Summerfield et al, 1983).…”
Section: Resultssupporting
confidence: 88%
“…This is a common characteristic in cowpea, as observed by Littleton et al (1979), Castro et al (1984), Phogat et al (1984) and Sivakumar et al (1996). Soon after, an accelerated vegetative growth was observed, with maximum values of LAI, observed and simulated, varying from 3 to 4.3, in 1997 and 1998, respectively.…”
Section: Resultsmentioning
confidence: 58%
“…From the same studies they have also described the pattern of accumulation and partition of dry weight and how this is influenced by the incident radiation, the fraction of the radiation intercepted and the efficiency with which it is used (Littleton et al 19796).…”
Section: Symposium Proceedings 1982mentioning
confidence: 99%
“…Littleton et al (1979) observed the rate of leaf appearance of cowpea plants grown in the field at Ibadan, Nigeria, from December 1973to March 1976 six experiments with only the cultivar TVu4552. Littleton et al (1979) observed the rate of leaf appearance of cowpea plants grown in the field at Ibadan, Nigeria, from December 1973to March 1976 six experiments with only the cultivar TVu4552.…”
mentioning
confidence: 99%
“…Littleton et al (1979) observed the rate of leaf appearance of cowpea plants grown in the field at Ibadan, Nigeria, from December 1973to March 1976 six experiments with only the cultivar TVu4552. Therefore, the phyllochron in the Littleton et al (1979) study was equal to 30°C. The rates were plotted against mean temperature, and the correlation coefficient was used to estimate the base temperature from a regression equation.…”
mentioning
confidence: 99%